Social responsibility of green microfinance institutions: A tool for promoting women’s economic empowerment in China - Pei, Jiuzheng (Technological and Economic Development of Economy, 2024)
Economic freedom has central importance among the nations, however, Chinese economic freedom index declining continuously, leading to the several issues. Particularly, economic freedom is low among the Chinese female population. The world average of economic freedom index in 2022 based on 175 countries is 60 index points, but the Chinese index is 48. To address this issue, this study introduced green microfinance institutions based on Mayoux’s Feminist Empowerment Theory. The objective of this study is to examine the role of green microfinance institutions in women economic freedom in China. A survey questionnaire is used to collect data from female clients of microfinance institutions. 315 respondents responded to the survey and data analysis is carried out by using Structural Equation Modeling (SEM). Results of the study identified that, green microfinance institution’s services such as credit and insurance can facilitate green micro enterprises. The promotion of green micro enterprises causes to increase women economic security, leading to the economic freedom. Additionally, green microfinance policy is a critical factor to promote the positive relationship between green microfinance institution’s services and women economic freedom. Findings of this are helpful for the practitioners to increase women economic freedom in China by providing various services of green microfinance institutions. First published online 18 March 2024